Development and Characterization of Knitted Fabrics for Better Sensorial Comfort Properties in Sportswear by Using Grey Rational Analysis. Issue 14 (28th October 2022) - Salman, Muhammad; Iftikhar, Fatima; Khan, Muhammad Qamar; Hussain, Tanveer; Ahmed, Naseer; Fazal, Muhammad Zohaib; Javed, Zafar; Naeem, Muhammad Salman
ABSTRACT: Sportswear textile is the interface between consumers, clothing and the environment in conjunction with human physiology. In this study, multi-response optimization of sensorial comfort properties of terry and fleece knitted sportswear fabrics was planned by varying areal densities (GSM) and fiber content under Taguchi-based gray rational technique. The L36 Taguchi orthogonal array was used to develop thirty-six samples out of which 18 samples were washed in order to determine the effect of washing, areal density and fiber content on sensorial comfort of fabrics. From the results it was revealed that washing process caused positive influence on crease recovery rate, smoothness score, and resilience while slight reduction in drapability and softness was observed after washing process. It was found that as the polyester content was increased from 20 to 40% the sensory characteristics of both terry and fleece fabrics were increased. Similarly, the areal density of fabric also caused significant influence on sensory attributes of clothing comfort. Based on Taguchi gray rational optimization, the optimum fabric parameters were found to be terry fabric, after wash, 240 GSM and 60/40 cotton: polyester content for simultaneously achieving good sensorial comfort properties for sportswear fabric.